Urbanity as a Process and the Role of Relative Network Properties—A Case Study From the Early Iron Age - Nakoinz, Oliver; Bilger, Michael; Matzig, David (Frontiers in Digital Humanities, 2020)
A manifold of concepts of urbanity have been discussed in the past and many criteria of towns have been developed. These criteria, e. g. size, population,legal aspects, way of life, structural and functional approaches are insufficient, because they cover just a part of the phenomenon and because they partly use fixed and arbitrary thresholds. We turn to an understanding of urbanity as a process which fills and shapes the scenery of the buildings and people and which involves complexity as one of the main drivers. In this sense we understand urbanity as a process of adaption to changed requirements or contexts in a complex settlement system, triggered by size, attracted by exemplary solutions and characterized by the emergence of new structures. With this paper we address the issues of relativity in the urbanity process. As adaption process, urbanity is relative in the sense, that other places may have gained better or worse adaption. Concerning networks, this means that network centrality measures have to be adapted to geographical networks. This paper applies this concept to the Princely Seats of the Early Iron Age with a special focus on the Heuneburg. A very limited part of the material culture is used to represent similarities and interaction between the different nodes. For this purpose we use fibulae which allow rather good dating and hence ensure a narrow time slice for the network analysis. Fibulae also provide a limitation to a certain social segment, which can be addressed as a middle class. This paper is intended to contribute to the problem of addressing the rather complex issue of urbanity using rather simple approaches such as network analysis. We pay attention to a tight integration of theory and method as well as to certain conceptual issues. This paper has two main results. First, we develop a consistent approach to apply social network centrality measures on geographical networks. Secondly, the role of a kind of middle class in the course of urbanity processes is enlightened.